Learning to build relationships for a better Australia Indigenous reconciliation in action in the construction and resource sectors - Heard, I.; Love, Peter; Sing, M.; Goerke, V. (Emerald, 2017)
© Emerald Publishing Limited. Purpose - Research examining the role of construction and involvement of resource organisations with indigenous reconciliation has been very limited in Australia. This paper aims to examine how a sample of organisations from Western Australia (WA) are engaging with indigenous reconciliation. Design/methodology/approach - Aquestionnaire survey juxtaposed with in-depth interviews are used to explore how construction and resource companies (mining and energy) operating in WA have been planning to build better relationships with the indigenous community as part of their corporate social responsibility (CSR) programme. Findings - The majority of construction and resource companies sampled embraced reconciliation as part of a contractual and legal requirement rather than part of their CSR. It was acknowledged that to effectively address the issues associated with reconciliation and indigenous engagement, there is a requirement for flexibility and adaption of existing protocols and processes to better suit the cultural differences that arise with interactions between indigenous and non-indigenous peoples. Research limitations/implications - The questionnaire survey was cross-sectional, and a limited number of in-depth interviews were undertaken. Respondents' opinions were sought about their organisations' reconciliation action plans, which have only been recently embraced by firms, and thus, views that were solicited should not be treated as being definitive. Originality/value - Research examining the role of construction and involvement of resource organisations with indigenous reconciliation in the construction and resource sector has been limited. The findings of this study can provide a platform for examining and comparing how construction and resource organisations in different countries are embracing the process of reconciliation with their indigenous peoples.